An Empirical Study of The Determinants of Audit Report Delay in Indonesia Banking Companies - Mimelientesa Irman; Restu Hayati; Lintang Nur Agia (Journal of Applied Business and Technology, 2020)
This study aims to analyze determinants of audit delay in banking companies listed on the Indonesia Stock Exchange (BEI). The analytical tool used is multiple linear regression models in 37 Indonesian banking companies from 2016 to 2018. Return on Asset, Debt to Asset Ratio, Auditor’s Opinion, and Firm Age are used as determinants of auditor delay. The result of the analysis shows that what affects audit delay in Indonesian banking is not based on the level of debt ratios or auditor opinion, but rather the level of profitability and company age A high level of profitability is good news that management wants to convey to stakeholders through the publication of financial audit reports that the company wants to convey quickly. The negative and significant effect between company age on audit delay shows that a company that has long been established and has experience and has better internal control management so that it can easily provide data for audience needs. Long established banks tend to have a large scale so that they have higher power and access to auditing firms to complete audits in a predetermined time.